The Effect Of Reading The Quran On Health - Aini, Syaripah (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2023)
This study reveals how the effects of reading the Koran on health, both physical health and mental health. Because when we read the Koran, it can have a positive effect on him, we will feel there is a feeling of satisfaction and peace of mind about the life we ​​live. Likewise, it will have an effect on the health of the body, because it can improve blood circulation and can stabilize blood sugar levels in the body. That is how it is felt by everyone who reads the Koran correctly. Reading the Qur'an filled with a sense of belief in Allah will lead to a process of self-surrender to the Creator which will bring about a passive state for the reader's body. In addition, reading the Koran like this will also cause a healthy placebo effect and reading the Koran itself can be a form of relaxation, which is called the transcendence meditation method. This relaxation does not focus on the process of relaxing muscles or other processes of physical relaxation, but on phrases that are repeated in a regular rhythm accompanied by self-surrender to God.